Parental Strategies For Overcoming Picky Eating Habits In Children Aged 2-3 Years - Alia Yulyanti; Titin Kusayang (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Picky eating habits in children aged 2-3 years often pose a challenge for parents. Children who exhibit selective eating behaviour tend to reject certain types of food, which can affect their nutritional adequacy and development. This study focuses on exploring the strategies used by parents in dealing with selective eating behaviour in young children. A qualitative approach with in-depth interviews was used as a research method to obtain more in-depth data from a number of parents who have children aged 2-3 years with selective eating habits. The results of the study show that parents apply various strategies, such as persuasive approaches, setting positive examples, varying food presentation, and consistency in applying eating rules. These strategies have been proven to help children become more open to trying different types of food. It is hoped that the results of this study can provide insights for parents and educators to support the positive development of children's eating patterns.